CIS 7 assessor competency course / Khairul Ammar Muhammad Ali - Muhammad Ali, Khairul Ammar (Unit Penerbitan FKAPP, 2020)
On the 12th March, Construction Industry Development Board (CIDB) Malaysia has conducted an Assessor Competency 3-day course at QLASSIC (Quality Assessment System in Construction) Academy, located at Kota Warisan in Sepang, Selangor. The purpose of this course is for the participants to understand Construction Industry Standard (CIS 7: 2014) which related to quality assessment system for building construction. Hence, it was divided into several modules. The course was accompanied with participants comprise of construction industry players. Among the shared modules are; 1. Introduction to Q-LASSICS, 2. Classification of Building Defects from Intemal/Extemal Architectural Aspect, and 3. Basic M&E fittings and external works. After the module is delivered, all the participants will be taught to evaluate the defects accordance with QLASSIC Standard through hands on using the prescribed tools.